Vectorial Diversity of Indoor-resting Mosquitoes in Damboa Town, Borno State, Nigeria: Implications for Disease Transmission and Control Strategies - Waseve Vandu-kwabe; David Bukbuk; Christiana Samuel Kwabe; Frank Abimbola Ogundolie; Daniel Makolo (UMYU Journal of Microbiology Research)
One of the reasons for the reemergence of yellow fever in Nigeria in 2017, twenty-one years after the last reported outbreak, was as a result of the presence of female mosquitoes, which serve as vehicles for the transmission of not only yellow fever virus but also other arboviruses, filarial worms, and protozoa, to susceptible human hosts. Female mosquitoes, particularly the indoor-resting, due to their blood-sucking nature, are responsible for sustaining the transmission cycles of arthropod-borne diseases, particularly in regions such as Damboa, where environmental conditions and inadequate control measures facilitate the breeding and survival of these mosquitoes. The predominance of blood-fed female mosquitoes within human habitation is, therefore, indicative of the heightened risk of arboviral outbreaks and calls for targeted interventions. This study was therefore carried out to assess the vectorial diversity of indoor-resting mosquitoes in Damboa Town, towards effective management and control of mosquito-borne diseases. Exactly 727 mosquitoes were collected indoors from human habitations in Damboa town of Borno State during the month of May to August according to the standard method described by the World Health Organization (WHO). Morphological examination of the mosquito revealed 92.30% Culex species, 7.15% Aedes aegypti, and 0.55% Anopheles gambiae. The females accounted for the majority (79.50%: 578/727) of the entire mosquito population, with 44.5% (257) being blood-fed, 6.0% (35) being gravid, 6.2% (36) being half-gravid, while 43.25% (250) were non-blood-fed. This study's findings suggest that as most female mosquitoes are blood fed, there is a high risk of mosquito-borne diseases and potential outbreaks, most especially in the absence of interventions. Therefore, this calls for an arbovirus surveillance system, mass vaccination against vaccine-preventable arboviral diseases, and the adoption of effective protective measures against mosquito bites by the individual human residents of Damboa, among other control measures.